Identifikasi Bahaya dan Risiko Pada Proses Memasak di Coffeshop X, Tangerang 2025 - Muhamad Rayhan; Rini Handayani; Putri Handayani; Ade Heryana (Pusat Riset dan Inovasi Nasional, 2025)
The cooking process in the food service industry, particularly in small businesses such as coffee shops, has the potential to pose various occupational safety and health (OHS) risks that are often not fully identified. This is important considering that the micro, small, and medium enterprise (MSME) sector has limitations in optimally implementing OHS standards. This study aims to identify the types of hazards and occupational risks in the cooking process at Coffeeshop X, Tangerang, as an initial effort to raise awareness of the importance of OHS implementation in the culinary sector. The method used is descriptive qualitative through direct observation and in-depth interviews with four informants involved in kitchen activities. The results show that the work stages in the kitchen include ingredient preparation, cooking, and plating, where each stage has different potential hazards. The identified hazards include mechanical hazards from using sharp knives, electrical hazards from equipment such as blenders, chemical hazards from using LPG, physical hazards from exposure to hot pans, biological hazards through cross-contamination, ergonomic hazards due to cramped workspaces, and psychosocial hazards arising from time pressure during rush hours. The risks include work accidents such as knife cuts and occupational diseases such as muscle aches. The study's conclusions underscore the importance of consistently implementing OHS standards, training on safe work practices, and routine supervision in coffee shop environments. These efforts aim not only to prevent workplace accidents but also to improve the quality of the work environment, productivity, and sustainability of culinary businesses in the MSME sector.